Vacuolar H(+)-pumping ATPase variable transport coupling ratio controlled by pH. - Davies, J M (1994)
The eukaryote endomembrane system contains a class of H(+)-pumping ATPase (H(+)-ATPases) of the vacuolar type (V-ATPases) that are responsible for the acidification of organelles. Their action is critical to numerous physiological processes, but the regulatory mechanisms that may control activity are not yet fully understood. The ratio of H+ transported per ATP hydrolyzed (n) has been determined thermodynamically for the red beet V-ATPase by using patch clamp. The value of n was found to range from 1.75 to 3.28 and was strictly dependent on cytoplasmic and lumenal pH. This suggests a mechanism by which V-ATPases are regulated by and might therefore control cytoplasmic and lumenal pH. Furthermore, the substantial capacity of plant vacuoles for H+ accumulation to pH 3 or lower can only be explained by the finding that n can adopt a value of < 2.